2013
DOI: 10.3109/15622975.2012.750014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive flexibility, central coherence and social emotional processing in males with an eating disorder

Abstract: Men with EDs share some of the intermediate cognitive phenotype present in women with EDs. Like their female counterparts, males with EDs show an inflexible, fragmented cognitive style. However, relative to healthy men, men with EDs do not have superior detail processing abilities, poor emotion recognition or increased sensitivity to social-threat. It is possible that gender differences in social-threat processing contribute to the female preponderance of EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 72 publications
(83 reference statements)
2
19
4
Order By: Relevance
“…We did not find that individuals with AN had a specific impairment in the recognition of facial expression of emotions, which is in line with some previous research [17, 20, 21, 33]. This research states that following other studies [11, 27] social perception in people with anorexia nervosa is largely preserved.…”
Section: Discussionsupporting
confidence: 91%
“…We did not find that individuals with AN had a specific impairment in the recognition of facial expression of emotions, which is in line with some previous research [17, 20, 21, 33]. This research states that following other studies [11, 27] social perception in people with anorexia nervosa is largely preserved.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study were consistent with previous research, demonstrating poorer global processing in AN, BN and unaffected AN relatives in comparison to HCs as evidenced by lower scores on central coherence indices [6,10,22,2931]. However, the findings are discrepant with a number of studies that report recall and copy data from the Rey figure as a measure of central coherence [32].…”
Section: Discussionsupporting
confidence: 81%
“…Two functional MRI studies that used a behavioral task in the scanner to assess neural response toToM task were not included as they were not designed to detect subtle deficits in social cognition . Having an unspecified type of EDNOS (1 sample from Medina‐Pradas et al), the inclusion of male patients, being reported as a conference abstract (1 study) and being based on an overlapping sample with an included study were other reasons for exclusion from the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%